Depiction of an Ascetic on the eastern wall of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The eastern wall of the garbhagriha (sanctum sanctorum) depicts the juxtaposition of the ascetic and the surasundari (celestial damsels). The ascetic is portrayed with a substantial jatabhara (matted hairdo) atop his head, along with a lengthy beard and moustache. His elongated earlobes signify a Mahapurusha lakshana (attributes), indicating him as a great individual. He is depicted with a bare upper body adorned with a broad yajnopavita (sacrificial thread), while his lower body is covered with a langoti (loincloth). His right hand appears damaged and raised, and he holds an unidentified object in his left hand.